(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2020)
The aim of this study is to examine the effect of temperature extraction on the potassium (K) and calcium (Ca) contents in orange and lemon peel extracts. The extractions were done at 62 ºC and 92 °C for 15 minutes and atmospheric pressure in distilled water. The fruit peel content in the extraction mixture was 5 % (w/v) in all samples. Calcium (Ca) and potassium (K) concentrations have been determined by flame photometric method. This research has revealed that by increasing the temperature of extraction, in particular, the concentration of Ca and K concentrations increased as applied extraction temperatures increased. The concentration of potassium is higher than the concentration of calcium in orange and lemon extracts, respectively. The concentration of K was 308 mg/l at 62 ºC and 361 mg/l at 92 ºC in lemon extracts, while in orange extracts the concentration of K was 476 mg/l at 62 ºC and 483 mg/l at 92 ºC. The concentration of Ca was 70.8 mg/l at 62 ºC and 71.9 mg/l at 92 ºC in lemon extracts, while in orange extracts the concentration of Ca was 91 mg/l at 62 ºC and 93.6 mg/l at 92 ºC. These results confirm that both citrus could be a very valuable source of potassium and calcium which are needed micronutrients to ensure the water and electrolyte balance and to build and maintain strong bones, proper function of muscles and nerves.